Archaeopedological analysis of colluvial deposits in favourable and unfavourable areas: reconstruction of land use dynamics in SW Germany. Issue 5 (30th May 2018) - Henkner, Jessica; Ahlrichs, Jan; Downey, Sean; Fuchs, Markus; James, Bruce; Junge, Andrea; Knopf, Thomas; Scholten, Thomas; Kühn, Peter
Abstract : Colluvial deposits, as the correlate sediments of human-induced soil erosion, depict an excellent archive of land use and landscape history as indicators of human–environment interactions. This study establishes a chronostratigraphy of colluvial deposits and reconstructs past land use dynamics in the Swabian Jura, the Baar and the Black Forest in SW Germany. In the agriculturally favourable Baar area multiple main phases of colluvial deposition, and thus intensified land use, can be identified from the Neolithic to the Modern times. In the unfavourable Swabian Jura increased colluvial deposition began later compared to the more favourable areas in the Baar. The same holds true for the unfavourable areas of the Black Forest, but intensified land use can only be reconstructed for the Middle Ages and Early Modern times instead of for the Bronze and Iron Age as in the Swabian Jura. Land use intensity and settlement dynamics represented by thick, multilayered colluvial deposits increase in the Baar and the Black Forest during the Middle Ages. In between those phases of geomorphodynamic activity and colluviation, stable phases occur, interpreted as phases with sustainable land use or without human presence.